(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Attempts were made to investigate different phytochemicals (secondary metabolites) of Clerodendron viscosum leaves extracts with different solvents e.g. petroleum ether (40-60° C), ethyl acetate and chloroform. The extracts were found to contain alkaloids, carbohydrates, flavonoids, glycosides, tannins and steroids. The extracts were then subjected to bioactivity against some stored grain insect such as Tribolium castaneus, Sitophiulus oryzae, Rhizopertha dominica using the method of residual film technique. Among the extracts, the petroleum ether extract showed higher toxicity against Sitophiulus oryzae and Rhizopertha dominica but moderate toxicity against Tribolium castaneus. The ethyl acetate and chloroform extracts showed moderate toxicity against Sitophiulus oryzae. The effectiveness of the order of toxicity of the extracts was found to vary with different intervals of treatments (24, 48 and 72 hours). Key words: Clerodendron viscosum; Phyto-chemical; Bioactivity; Stored grain insect; Probit mortality DOI: 10.3329/bjsir.v45i4.7385 Bangladesh J. Sci. Ind. Res. 45(4), 381-386, 2010